Kajian Adaptasi Gereja Katolik pada Interior Bangunan Tionghoa Menjadi Gereja Santa Maria De Fatima Jakarta - Gabriella Maria (Intra, 2017)
Santa Maria De Fatima Church once was a traditional Chinese residence that belonged to a Chinese noble located in Chinatown so this building is still preserves its Chinese style. This research is an interesting object to study because this traditional Chinese residence was refunctioned into a Catholic Church. This research’s aims are to understand the adaptation process that has been occurred between Catholic and Chinese culture in the interior of the church and also to find out how much the adaptation have taken place. This research was done by an observational method by collecting data through literature, interview, observation, and documentation. The results indicate that the adaptation process between Catholic and Chinese have occurred in the church. Catholic elements that have undergone adaptation interior are the building, facade, building organization, partition, candle table, tabernacle table, tabernacle, statues of lion stone, pillar, peony flower, roof consul, and accessories. Chinese elements that have undergone adaptation are layout and sedilia. The elements that adapt to each other on the church are spatial elements, transition elements, altar table, pulpit, lighting, meandering carvings, and wall illustrations. While the elements that aren’t adapt on the church are building directions, congregations’ bench, acolytes’ chair, and holy lamp.